Membangun Karakter untuk Memerangi Bullying: Inisiatif Guru dalam Pendidikan Anak Usia Dini - Salehuddin, Shafira Nurulita; Ishaq, M.; Aisyah, Eny Nur (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study aims to explore teachers' efforts in building character to overcome bullying behavior in early childhood education. The focus of this study is the strategy for implementing effective character education. This study uses a descriptive qualitative approach. Data collection through observation and interviews. Data analysis is carried out through the stages of data condensation, data presentation, and verification. The results of the study show that teachers' efforts are integrating character education through problem-based learning, projects and direct practice, creating school welfare, identifying bullying, and involving parents in supporting children's character formation. This strategy shows effectiveness in building empathy, concern, and positive behavior in early childhood. The implication of this study is that a holistic approach is needed involving teachers, parents, and the school environment. These findings can be a reference for the development of more inclusive and contextual character education policies for children.